Edward Taylor (1884 - 1984). Sympozjum w PTPN - Nowakowski, Zygmunt Konrad; Zakrzewski, Zbigniew (Wydział Prawa i Administracji UAM, 1985)
On the hundredth Anniversary of the birthday and the twentieth Anniversary of the death of prof. Edward Taylor a solemn Symposion took place at the Poznan Society of the Friends of Sciences (PTPN). Opening the symposion, prof. Zakrzewski recalled the main stages of scientific and social life of that scholar. The debates were presided by the Chairmen of the History and Social Sciences Department at the PTPN — prof. Zygmunt Konrad Nowakowski. The symposion consisted of two parts. The first one was devoted to a pronouncement of earlier elaborated papers while the second brought occasional pronouncements and appearances. At the conclusion of debates two resolutions were adopted to celebrate the memory of the late prof. Edward Taylor. The first one, directed to the President of Poznań, is applying to name one of the city streets after Edward Taylor and the second one designing a foundation of commemorating plate by the Professor's disciples and situating it in a suitable place.
Edward Taylor (1884-1984). A Symposium in the PTPN